Melanoma trials that defined surgical management: Overview of trials that established NCCN margin guidelines. Issue 1 (13th December 2021) - Sharib, Jeremy; Slingluff, Craig L.; Beasley, Georgia M.
Abstract: Since the observation that clearance of all visible and microscopic tumors from cutaneous melanoma is critical to prevent a recurrence, wide surgical margins have been central to surgical dogma. In the last several decades, more conservative margin widths have been vigorously studied by surgical investigators to lessen wound complications, the need for reconstruction, and healthcare costs. This review summarizes surgeon‐led clinical trials that define current guidelines and highlights the challenges to initiate and perform trials today.